The understanding of doctors and nurses’ roles in Islamic medical practice and ‘Rukhsah Salah’ in a shariah friendly hospital - Mohd Arifin, Siti Roshaidai; Mohd Nazir, Nur Afiqah; Daud, Normadiah; Samsudin, Suhaiza (2021)
The medical service quality could be influenced by various factors such as medical care etiquettes, healthcare practitioners’ quality and healthcare practitioners’ advice. The implementation of Islamic healthcare services within Shariah-compliant hospital faces some challenges due to a lack of awareness, ethics and spirituality among healthcare practitioners. Despite these challenges, less attention has been given to the healthcare practitioners’ perspectives of their roles in delivering such services. The aim of this study was to assess the understanding of healthcare practitioners on their roles in Islamic medical practice in a Shariah-compliant hospital. This descriptive cross-sectional study was conducted among 152 nurses and doctors in a Shariah friendly hospital in Pahang, Malaysia, using a set of questionnaires related to the understanding of Islamic medical practice and knowledge of Rukhsah Salah. Whilst 80.3% (n=122) participants had a high level of understanding of Islamic medical practice, only 50% (n=76) had a good level of knowledge regarding Rukhsah Salah. Their departments (ward/ clinic disciplines), age, and years of experiences significantly associate with the level of understanding of Islamic medical practice with p-values of 0.04, 0.05 and 0.02, respectively. The department is also significantly associated with the level of knowledge regarding Rukhsah Salah (p-value < 0.001). The findings from this study suggested that more training on Rukhsah Salah should be designed for nurses and doctors working in a Shariah friendly hospital to support the implementation of Islamic medical practice